Polymers and Ionic Liquids Shaping up a New Generation of High Performances Nanomaterials - Duchet-Rumeau, Jannick; Gérard, Jean-François; Livi, Sébastien (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The main objective of polymer materials scientists is to develop and design high performance polymer-based materials via the introduction of block copolymers, ionomers or inorganic-organic hybrids, in order to introduce functionalities such as mechanical reinforcement, gas barrier properties, fire retardancy, shape memory behavior or self-healing ability. In the last ten years, ionic liquids have demonstrated huge potential as new components within polymer-based materials, leading to a wide range of applications. Due to their many physical-chemical properties, as well as their various possible combinations, ionic liquids represent a new path to produce multifunctional materials.